A severe case of sepsis and pneumonia caused by Leptospira in a previously healthy 23-year-old man from Cuba: A case report with literature review - Enrico Perugini; Tommaso Ascoli Bartoli; Stefania Carrara; Gaetano Maffongelli; Laura Scorzolini (One Health)
Leptospirosis is a re-emerging zoonotic disease that poses significant threats. Its nonspecific symptoms can mimic other febrile illnesses, complicating diagnosis, especially in low-endemic regions like Europe, where clinical awareness among healthcare providers may be limited. Diagnostic challenges also arise in low-resource settings due to restricted access to appropriate testing. Specific antimicrobials are the cornerstone of medical treatment, while the role of systemic steroids in severe cases remains undefined. We present a case of severe sepsis and pneumonia caused by Leptospira in a previously healthy 23-year-old male from Cuba. The main characteristics of the case include severe lung involvement, with the development of respiratory failure despite two days of potentially effective antimicrobial therapy, and the favorable outcome achieved with a combination of intravenous steroids, targeted antibiotic treatment and supportive measures.